2021
DOI: 10.1128/aem.01674-21
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Two Stator Systems in the Flagellar Motor of Pseudomonas aeruginosa Studied by a Bead Assay

Abstract: We developed a robust bead assay for studying flagellar motor behavior of Pseudomonas aeruginosa . Using this assay, we studied the dynamics of the two stator systems in the flagellar motor. We found that the two sets of stators function differently, with MotAB stators providing higher total torque, and MotCD stators ensuring more stable motor speed. The motors in wild-type cells adjust the stator compositions according to the environment, resulting in an optimal performance in environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 70 publications
5
19
0
Order By: Relevance
“…Under increased load, presumably more MotCD stators are recruited to the motor, increasing the torque to such an extent that occasional wrapped mode formation can be observed. This agrees with the observation that also in P. aeruginosa , less MotCD stators bind to the motor during operation in a low viscosity environment (26).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Under increased load, presumably more MotCD stators are recruited to the motor, increasing the torque to such an extent that occasional wrapped mode formation can be observed. This agrees with the observation that also in P. aeruginosa , less MotCD stators bind to the motor during operation in a low viscosity environment (26).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, for P. aeruginosa it was shown that under increased load on the flagella, more MotCD units are recruited to the motor (26). An increased viscosity thus only leads to a decrease in motilty for the ∆motAB mutant and the wild-type while it abolishes motility in the ∆motCD mutant for 15% Ficoll (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By tracking the circular swimming of individual cells near the glass surface ( 18 ) ( Movie S2 ), we confirmed that the filament of P. aeruginosa maintained a fixed left-handed chirality in pull and push modes ( 19 ). When the motor rotates CCW (viewed from tail of the filament), the filament pushes the cell forward; otherwise, the filament pulls the cell forward ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 61%
“…The proposed mechanism does not require the presence of a mechanosensitive domain within the stator unit, and it is consistent with a strong chemical affinity between the PGB and the peptidoglycan ( Roujeinikova, 2008 ). In some bacterial species, such as Pseudomonas aeruginosa , which carries more than one type of stator, the viscous load modulates competitive docking of stator units at the motor ( Wu et al, 2021 ). The outcome of the competition between different stator types will be determined by differences in the torsional rigidity of stator components, the rigidity of the peptidoglycan network, the amount of torque each stator type can generate against a particular load, the ionic strength, and the relative affinities of the different PGB domains for the cell wall.…”
Section: Introductionmentioning
confidence: 99%